Ice Camp Surface Mesonet NCAR PAM-III, Maui site (PRELIMINARY)(GIF). Version 1.0 [PRELIMINARY] - Andreas, E.; Fairall, C.; Guest, P.; Persson, O.; U.S. Army Cold Region Research Laboratory (UCAR/NCAR - Earth Observing Laboratory, 2007)
NCAR portable automated mesonet (PAM-III) station (Maui site). One of six stations deployed in the vicinity (within 5 km) of the SHEBA Ice Camp. Other stations are Atlanta, Baltimore, Cleveland, Florida, and Seattle. Station measures pressure, temperature, relative humdity (RH), wind speed and wind direction, energy budget parameters (4) and energy flux parameters (3). This data set contains preliminary data. The final data sets are 13.838 and 13.839.
Keywords: climatologyMeteorologyAtmosphere; Surface; Arctic; Land Based; Flux; Meteorology; Flux Tower; Portable Automated Mesonet - PAM; In Situ Land-based Platforms > MOBILE STATIONS/VEHICLES > PAM > Portable Automated Mesonet > 7fe65a2b-756a-43a7-8ee6-d9ff2eb33f4c; Sonic Anemometer; In Situ/Laboratory Instruments > Current/Wind Meters > > > SONIC ANEMOMETER > > 46a263bf-4448-421f-be9d-7628f3d03490; Radiometers; Earth Remote Sensing Instruments > Passive Remote Sensing > Spectrometers/Radiometers > Radiometers > RADIOMETERS > > 184150ce-100e-485b-87db-839615af3d1a; EARTH SCIENCE > TERRESTRIAL HYDROSPHERE > SNOW/ICE > SNOW/ICE TEMPERATURE; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WATER VAPOR > WATER VAPOR INDICATORS > HUMIDITY > RELATIVE HUMIDITY; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC WINDS > SURFACE WINDS > WIND DIRECTION; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC PRESSURE > SURFACE PRESSURE; EARTH SCIENCE > TERRESTRIAL HYDROSPHERE > SNOW/ICE > SNOW ENERGY BALANCE; EARTH SCIENCE > ATMOSPHERE > CLOUDS > CLOUD DYNAMICS > RADIATIONAL COOLING; EARTH SCIENCE > ATMOSPHERE > ATMOSPHERIC TEMPERATURE > SURFACE TEMPERATURE > AIR TEMPERATURE; Arctic Ocean; SHEBA Ice Camp; SHEBA; Surface Heat Budget of the Arctic Ocean Project; S - U > SHEBA > Surface Heat Budget of the Arctic Ocean > af6c4ef7-c65e-4adb-a075-0ea9144dea95